Successful difficult airway management of a child with Coffin‐siris syndrome - Ozkan, Ahmet Selim (Clin Case Rep, 2017)
Management of airway in patients who have Coffin‐Siris syndrome (CSS) is often problematic because most of these patients have difficult airway. NTI via C‐MAC VL is an useful alternative to direct laryngoscope for orotracheal intubation in airway and anesthetic management in a case of CSS. Alternative airway devices should be readily available.